Geographic variation in gene flow from a genetically distinct migratory ecotype drives population genetic structure of coastal Atlantic cod (Gadus morhua L.). (21st June 2022) - Breistein, Bjoerghild; Dahle, Geir; Johansen, Torild; Besnier, Francois; Quintela, Maria; Jorde, Per Erik; Knutsen, Halvor; Westgaard, Jon‐Ivar; Nedreaas, Kjell; Farestveit, Eva; Glover, Kevin Alan
Abstract: Identifying how physical and biotic factors shape genetic connectivity among populations in time and space is essential to our understanding of the evolutionary trajectory as well as the management of marine species. Atlantic cod is a widespread and commercially important marine species displaying several ecotypes with different life history strategies. Using three sets of SNPs: neutral, informative, and genome‐inversion linked, we studied population genetic structure of ~2500 coastal Atlantic cod (CC) from 40 locations along Norway's 2500 km coastline, including nine fjords. We observed: (1) a genetic cline, suggesting a mechanism of isolation by distance, characterized by a declining F ST between CC and North East Arctic Cod (NEAC—genetically distinct migratory ecotype) with increasing latitude, (2) that in the north, samples of CC from outer‐fjord areas were genetically more similar to NEAC than were samples of CC from their corresponding inner‐fjord areas, (3) greater population genetic differentiation among CC sampled from outer‐fjord areas along the coast, than among CC sampled from their corresponding inner‐fjord areas, (4) genetic differentiation among samples of CC from both within and among fjords. Collectively, these results permit us to draw two main conclusions. First, that differences in the relative presence of the genetically highly distinct, migratory ecotype NEAC, declining from north to south and from outer to inner fjord, plays the major role in driving population genetic structure of the Norwegian CC. Second, that there is limited connectivity between CC from different fjords. These results suggest that the current management units implemented for this species in Norway should be divided into smaller entities. Furthermore, the situation where introgression from one ecotype drives population genetic structure of another, as is the case here, may exist in other species and geographical regions, thus creating additional challenges for sustainable fisheries management.